Response of White Seabass to Practical Diets with Varying Levels of Protein. (15th November 2013) - Jirsa, Dave; Davis, D. Allen; Barrows, Frederic T.; Roy, Luke A.; Drawbridge, Mark
Abstract: Interest in the commercial culture of White Seabass Atractoscion nobilis on the western coast of the United States has been increasing in recent years. Despite this interest, there is a scarcity of knowledge on the dietary requirements of this species, particularly as it relates to basic nutrient requirements and selection of feeds. Hence, we evaluated a wide range of protein levels (31, 34, 37, 40, 43, and 46%) with practical lipid levels (5.75, 7, 8.25, 9.5, 10.75, and 12%) to initiate the development of a species‐specific commercial diet for White Seabass. A 56‐d trial was conducted in a recirculating system at Hubbs–SeaWorld Research Institute's marine fish hatchery in Carlsbad, California. Diets were formulated to contain 20–30% fish meal and offered to juvenile White Seabass (3.6 g mean initial weight). At the conclusion of the growth trial final weights ranged from 13.9 to 15.9 g, and percent weight gain ranged from 278.2% to 345.6% and generally increased with protein level. Protein retention ranged from 25.2% to 33.7% and was significantly lower for fish offered the diets containing 43% and 46% protein. Based on growth and protein retention, the use of a diet incorporating 40% protein and 10% lipid is recommended for juvenile White Seabass.